Sortana: Tradisi Pasca-Kematian di Kota Pamekasan Berdasarkan Prespektik Strukturalisme Levi Strauss - PS., Mawar; Hermanda, Febriaty (Postgraduate Studies UIN Sunan Ampel Surabaya, 2024)
Myth holds a powerful place in Javanese-Madurese society, particularly in the Pamekasan region. This myth represents a cultural heritage passed down from ancestors, such as the Sortana tradition—a post-death ritual practiced in Pamekasan. This study aims to uncover the structural elements of the Sortana tradition within Madurese culture, especially in Pamekasan, through the lens of Claude Lévi-Strauss’s Structuralism theory. The research employs a qualitative approach with a phenomenological method, focusing on the Sortana phenomenon that continues to be preserved and believed in by the Madurese community. The findings reveal that the Sortana tradition is not merely a matter of following customary practices; rather, it embodies underlying elements intended to ensure the comfort of the deceased in their new world—from the first day, the fortieth day, up to the thousandth day, marking their final day in the earthly realm. Moreover, Sortana also serves as an expression of gratitude and charity from the deceased to those who have attended to their burial rites—from purification and interment to the prayers offered in the days that follow.